MO119COMPUTER-DERIVED SOFTWARE IN CLINICAL PRACTICE: RESULTS FROM A SHORT-TERM FOLLOW-UP ACCORDING TO KIDNEY STONE COMPOSITION IN KIDNEY STONE FORMERS. (29th May 2021) - Cunha, Tamara; Rodriguez, Adrian; Ferraro, Pietro Manuel
Abstract: Background and Aims: Urinary supersaturation (SS) contributes to stone formation, and its assessment in stone formers may be helpful in clinical practice. Several computer programs are available for SS calculation, including EQUIL2, JESS and Lithorisk1 . The aim of this study was to evaluate changes in SS in 24-hour urine in patients with known stone composition before and after about three months of regular treatment. Method: Patients who submitted their stone/s for composition analysis and had provided an adequate 24-hour urine collection (creatinine 15-20 mg/kg/24-hour) before and around 90 days under regular treatment were included. Stone composition was defined using morphoconstitutional and infrared spectroscopy. The treatment was initiated in accordance with specific guidelines, and included dietary advices and medications2 . SS for calcium oxalate (CaOx), calcium phosphate (CaP) and uric acid (UA) using EQUIL2, JESS and Lithorisk were calculated at baseline and after about 90 days on treatment. Continuous variables were reported as means (SD) while categorical variables were reported as frequencies and percentages. Baseline and follow-up SS urine values were compared using the Wilcoxon signed-rank test. 3D graphs were plotted using mean SS values of CaOx, CaP and UA obtained from each program before and after treatment, dividing the stones into 4 groups1 : calcium oxalate monohydrate (COM), calcium oxalate dihydrate (COD), calcium phosphate (CaP), and uric acid (UA). Ethical Committee approval was obtained. Results: 105 patients (61 men, 58%) were followed and provided 24h urine collection. Of these, 101 (96%) were recurrent patients. The mean (SD) follow-up was 94 (14) days. 48 (46%) of all calculi were made of CaOx, either COM or COD, 36 (34%) of UA, and 21 (20%) of CaP. A significant reduction in SS values during treatment was observed in patients with COM (p<0.05), COD (p<0.001), and UA stones (p<0.001) with all programs. The reduction in SS values over time in patients with CaP stones was not significant (Table 1 ). Figure 1 shows 3D plots with SS before and after treatment into 4 groups of stone formers. Conclusion: EQUIL2, JESS and Lithorisk are suitable software currently used for clinical and research purposes. SS values calculated by EQUIL2, JESS and Lithorisk during follow-up showed a significant reduction among COM, COD and UA stone formers. CaP stone formers did not show significant changes in SS over time.